The Impact of the Dutch Euthanasia Act on the Number of Requests for Euthanasia and Physician Assisted Suicide - A Cohort Study in General Practice Between 1977 and 2007 - Donker, G.A.; Alphen, J.E. van (IntechOpen, 2011)
None